LA NEGOCIACIÓN COLECTIVA ESPAÑOLA ANTE EL RETO DEL TELETRABAJO - Gallego Moya, Fermín (Revista de Derecho, 2022)
It is the Collective Agreement’s mission to adapt the legal system to the ever-changing socio-labour reality, something which is not undertaken in a timely manner. The challenge of updating the conventional instrument as a normative source is a complicated one, especially if barely sketched legal constructions that require rapid regulation burst into the complex negotiating equilibrium without warning. In the last year, it is quite clear that working from home has been one of those changes, unexpected in its rapidity, it has become the star of the global labour law debate. Studies, commentaries, news and analyses have dealt with it from all points of view, both in specialised areas and in the general media. Logically, the various regulatory authorities and the social partners have also paid close attention to it, and the latter have been assigned a very important role in the implementation of a regulation that is as new as it is necessary. In Spain, Royal Decree Law 28/2020 and the subsequent Law 10/2021 on remote working have made a firm commitment to sectoral intervention in the development of a new and brief legal framework, and the purpose of this paper is to analyse this delegation and, consequently, to verify the degree to which collective bargainers have taken up this new challenge. The successful implementation of this form of work provision will depend to a large extent on the level of commitment of the latter.
Keywords: collective bargaining; current challenges; remote working